Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa Pada Pembelajaran Pendidikan Pancasila Kelas IV SD Negeri Glagah Yogyakarta - Mali, Maria Anjelica; Pratomo, Wachid; Nugroho, Irfan Adi; Nofrida, Eka Ridha; Megawati, Ida (Journal of Contemporary Issues in Primary Education, 2025)
The Effect of Problem Based Learning Model on Student Learning Outcomes in Pancasila Education Learning for Grade IV of Glagah Elementary School, Yogyakarta. This study aims to determine the effect of the Problem Based Learning model on Student Learning Outcomes in Pancasila Education Learning for Grade IV of Glagah Elementary School, Yogyakarta. This study is a type of quantitative research with a quasi-experiment. The sample in this study was 55 grade IV students. Which is divided into two groups, namely 27 students in the experimental class who use the problem based learning model and 28 students for the control class who use the discovery learning model. Data collection techniques consist of observation, tests, documentation. For research instruments  test instrument sheets consisting of pretest and posttest. The validity of the questions hasbeen tested and obtained 20 valid questions and 5 invalid questions. Data analysis techniques are carried out through normality tests, homogeneity tests, hypothesis tests. The results of this study indicate that the Problem Based Learning model applied has been proven to improve student learning outcomes. This can be seen from the increase in the average value of Pre-test and Post-test in the experimental class, which was 12.22 increasing to16.33. The Problem Based Learning model has also proven to be more effective than the previous model that has been applied in the control class. This can be proven by comparing the post-test results of the experimental class and the control class, where the average value of the post-test of the experimental class was 16.22. While the control class was 14.92. Based on the results of the Independent Sample T-test, the significance value of thepost-test was 0.006 <0.05, which means there is a significant difference between the two classes.